Dental Management of Cardiovascular Compromised Patient - Sadiq, Omar; Ghoul, Rand; Muhamad, Abu-Hussein (Journal of Neonatal Surgery, 2025)
Cardiovascular diseases (CVD) comprise of a group of diseases of the heart and vascular system affecting majority of individuals worldwide. Relation between oral health and cardiac diseases has been well established. Common cardiac disorders encountered in a dental practice include arterial hypertension, heart failure, ischemic heart disease, cardiac arrhythmias, infective endocarditis, stroke, and cardiac pacemaker. Patients with CVDs pose a significant challenge to dental therapy. These patients need special considerations and an adequate understanding of the underlying cardiovascular condition to provide safe and effective dental treatment.The present study consists of a literature review dental management of patients suffering from various cardiovascular diseases